Postharvest shelf life enhancement of peach fruit treated with glucose oxidase immobilized on ZnO nanoparticles. (1st January 2022) - Batool, Razia; Kazmi, Syed Akif Raza; Khurshid, Shazia; Saeed, Muhammad; Ali, Sikandar; Adnan, Ahmad; Altaf, Faizah; Hameed, Aminah; Batool, Farwa; Fatima, Noor
Graphical abstract: Highlights: Postharvest handling is an important determinant of fruit shelf life. Glucose Oxidase is an important alternate to chemical antioxidants in food industry. Covalent Immobilization of glucose oxidase increases its stability. Glucose oxidase immobilized on ZnO nanoparticles extends the Shelf Life of Peach. Abstract: For the shelf life extension of fruits, we envisioned a novel antimicrobial approach that is based on the production of a thin layer of hydrogen peroxide at the surface of food by utilizing the bioactivity of glucose oxidase (GOx). The enzyme, purified from Aspergillus Niger, was immobilized on zinc oxide nanoparticles and then suspended in a buffer to prepare a spraying solution of GOx/ZnONPs. Post-immobilization analyses indicated that immobilized enzyme showed higher activity as compared to the free enzyme. The GOx/ZnONPs spray was applied for postharvest treatment of peach. The control and treatment groups were stored at ambient conditions for fifteen days and standard quality parameters were analyzed. In contrast to the control group, the GOx/ZnONPs spray treatment was remarkably effective in maintaining the physiological appearance of fruits even more than 12 days and showed a significant reduction in the decrease of weight, firmness, TSS, and DPPH free radical scavenging activity of fruits. Thus GOx/ZnONPs is an excellent platform to extend the postharvest shelf life of peach.